The Effect of Online Learning Based On Socio Scientific Issues (SSi) On Improving Learning Independence and Critical Thinking Students Faculty of Education and Education Science Universitas Muhammadiyah Sumatera Utara in The Pandemic Covid-19 - Irfan Dahnial (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2021)
This study aims to see the results of how much the effectiveness of students in the online-based learning process based on the results of the data above, the independence of online-based learning in learning the Indonesian democracy system is strong response with a percentage of 63%, while some other students respond strongly to the percentage of 31%, responding quite 5% and respond weakly 1%. The average result of student response questionnaire is 99%. Thus it can be concluded that the response of students to learning independence in learning the Indonesian democratic system is strong. This type of research uses quantitative research in which researchers decide to determine what will be studied, ask narrow specific questions, collect quantitative data (can be calculated) from participants, analysis using statistical figures and conducting investigations in an impartial or objective way Creswell, (2008: 46). That is, research using a quantitative approach has advantages in a measurable research process with more objective results. Based on the above explanation it can be concluded that the quasi experimental design is a type of research design that has a control group and the experimental group is not randomly selected. Researchers use quasi experimental design because in this study there are variables from outside that cannot be controlled by the researcher.